Palliative Care in AIDS Cases - Carmen Manciuc; Cristina Nicolau; Janny Liviu Prisacaru; Carmen Dorobat (Romanian Society of Oral Rehabilitation, 2010)
Terminal stages of AIDS must enjoy special attention and care for both patients and their relatives. Material and method: There were studied retrospectively case report forms of patients who died of AIDS in the Infectious Diseases Clinic of Iasi. In the department of HIV-infected patients of the Infectious Diseases Hospital of Iasi, within the last 3 years (2007-2009) there were 28 deaths, with an average of 9 patients per year. Most of them died of multiple organ failure, in the final stage of AIDS (10 cases), meningeal coma (5 cases) or respiratory failure during the terminal pulmonary pneomocystosis TB (13 cases). The palliative therapy was conducted throughout the hospitalisation of the terminal stage. The patients who survived longer required psychological support from admission until they lost their state of consciousness - they were 23 in number, with a duration of psychological palliation from 2 to 32 days. Objectives: Establishing a team and protocols of palliative care for these patients. Conclusions: Palliative care, in cases of terminal AIDS disease, must be conducted by a team including specialists in infectious diseases, in intensive care, psychologists and it also addresses the patients' families.